FACTORS INFLUENCING MUTTON PRODUCTION IN TAMIL NADU - Palanichamy, V; Selvakumar, K N; Prabu, M; Pandian , A Serma Saravana (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
A study was carried out on the factors influencing mutton production in sheep farming in different categories of farms in southern districts of Tamil Nadu. Cobb-Douglas production function was used to identify the factors contributing to the efficiency in sheep production per flock in the study area. The results of the production function analysed for overall farm category showed that the co-efficient of multiple determination (R2) was 0.884 indicating that 88.4 per cent variations in the mutton production can be attributed to the independent variables chosen for the study. The flock size was the important factor influencing the sheep farming, since regression co-efficient (0.705) for this variable is statistically significant at 1 per cent level. As for as the estimates for labour charge and health care charges are concerned their respective regression co-efficients (0.086 and 0.291) were statistically significant at 1 per cent level (p
Keywords: Mutton production; Cobb-Douglas Production function; Flock size